Deposition Pattern and Toxicity of Subcutaneously Im planted Uranium Dioxide in Rats - Molinari de Rey, Beatriz L.; Lanfranchi, Héctor E.; Cabrini, Rómulo Luis (Pergamon Press Ltd., 1984)
Fil: Molinari de Rey, Beatriz L. Comisión Nacional de Energía Atómica; Argentina